Corrosion and health aspects in ohmic cooking of beef meat patties. (February 2015) - Wang, Ruogu; Farid, Mohammed M.
Highlights: Combined ohmic and plate cooking can reduce cooking time and makes the process energy efficient. Combined ohmic and plate cooking of meat patties produces safer products. Corrosion of plates in ohmic cooking can be reduced significantly by applying high frequency power. Iron, chromium and nickel transfer from the cooking plates to meat at different rates. Abstract: Ohmic cooking process is based on passing electric currents through the food causing internal heat generation. Previous research has shown that combined ohmic and conventional heating could reduce cooking time of meat patties. However, pitting corrosion was observed on the electrode plates after cooking, influencing the safety of food product. In this work, selected parameters (50 Hz and 10 kHz frequencies) were used to determine the impact of the frequency on corrosion of different stainless electrode plates. Visual observation of the corroded stainless steel 316L electrode plates and metal ions concentrations in cooked patties showed that higher frequency decreased the corrosion in ohmic cooking significantly. More importantly, the results showed that nickel and chromium ions transfer from the stainless steel plates to the meat at much lower rate compared to iron ion, leading to chromium and nickel ions concentrations in the cooked meat within the safe limit when high frequency power is used.